2015
DOI: 10.1128/jvi.02612-14
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Flavivirus Population Diversity by RNA Interference

Abstract: bTo test the hypothesis that RNA interference (RNAi) imposes diversifying selection on RNA virus genomes, we quantified West Nile virus (WNV) quasispecies diversity after passage in Drosophila cells in which RNAi was left intact, depleted, or stimulated against WNV. As predicted, WNV diversity was significantly lower in RNAi-depleted cells and significantly greater in RNAistimulated cells relative to that in controls. These findings reveal that an innate immune defense can shape viral population structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 35 publications
0
38
0
Order By: Relevance
“…Following stochastic reductions in genetic diversity, we observed rapid recovery in virus population size and diversity during expansions in the next tissue/compartment that was likely promoted by RNAi (Brackney et al, 2009; Brackney et al, 2015). However, our data does not support that differences in RNAi targeting were responsible for the differences in intra-tissue divergence detected among species.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Following stochastic reductions in genetic diversity, we observed rapid recovery in virus population size and diversity during expansions in the next tissue/compartment that was likely promoted by RNAi (Brackney et al, 2009; Brackney et al, 2015). However, our data does not support that differences in RNAi targeting were responsible for the differences in intra-tissue divergence detected among species.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have assessed how different host types impact WNV population structure, and have shown that WNV populations are more diverse in mosquitoes compared to birds (Grubaugh et al, 2015; Jerzak et al, 2005; Jerzak et al, 2007). In mosquitoes, purifying selection is weak and virus diversification is driven by the action of RNA interference (RNAi), which creates an intracellular milieu that favors rare genotypes (Brackney et al, 2009; Brackney et al, 2015). In contrast, purifying selection in birds is strong (Jerzak et al, 2008) and the innate antiviral responses are dominated by type I interferon.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence suggests that viral genome diversity is critical for the adaptation of flaviviruses and other arboviruses to new and changing environments and hosts [58]. Brackney and colleagues (2015) then determined that the siRNA pathway imposes diversifying selection on WNV genomes in infected Dm S2 cells [59]. S2 cells were used since Ago2 and Dicer2 depletion with cognate dsRNAs is well-established.…”
Section: Viral Counterdefenses To the Sirna Pathwaymentioning
confidence: 99%
“…They then determined WNV quasispecies diversity in an amplicon spanning the 5′ untranslated region (UTR)-capsid-premembrane genes of WNV RNA from populations produced after a single round of infection or after five passages in Dm S2 cells. WNV diversity was significantly lower in the targeted sequence of WNV in RNAi-depleted cells but significantly greater in RNAi-stimulated cells relative to that of the intact controls [59]. They hypothesized that targeting viral genomes with siRNAs can lead to the rapid emergence of escape mutants containing mutations within intensely-targeted sequences leading to increased genome diversification of the virus.…”
Section: Viral Counterdefenses To the Sirna Pathwaymentioning
confidence: 99%
“…It has even been possible to select for strains of P. gallinaceum, a parasite normally transmitted by Culex spp., that can be transmitted by an anopheline mosquito (36). Selection of arboviruses by the mosquito innate immune defense has also been demonstrated (9).…”
Section: Evidence Of Plasmodium Adaptation To Mosquito Vectorsmentioning
confidence: 99%